Disinfection of Orthodontic Elastomers and Its Effects on Tensile Strength - Leandro Berni Osorio; Luiz Makito Osawa Gutierrez; Eduardo Martinelli de Lima; Eduardo Gonçalves Mota; Luciane Macedo de Menezes (Galenos Yayinevi, 2022)
Objective: This study aimed to investigate the effect of different disinfection protocols on the mechanical properties of orthodontic elastomeric ligatures (EL), an important issue to biosafety improvement and infection control, and to avoid cross-contamination.Methods: A total of 120 EL were randomly divided into 6 experimental groups (n = 20) according to the disinfection method employed: group 1, EL were not immersed in a disinfectant solution (control group); group 2, EL were immersed in 2% glutaraldehyde; group 3, EL were immersed in 70% alcohol solution; group 4, EL were cleaned in an ultrasound washing (UW) machine by immersion in 0.5% enzyme detergent solution; group 5, UW procedure was performed, followed by immersion in 2% glutaraldehyde; Group 6, UW procedure was performed, followed by immersion in 70% alcohol. After disinfection, EL were subjected to a tensile strength test where the maximum strength, maximum elongation, and work at failure were determined. Data were statistically evaluated using one-way ANOVA and Dunnett's t-test for multiple comparisons.Results:Statistically significant different (P < .05) values were found between the disinfection methods, and 70% alcohol showed negative changes in all mechanical properties of orthodontic elastomers. By contrast, 2% glutaraldehyde did not show significant alteration in mechanical properties, whereas the UW procedure showed significant alteration in maximum strength and work at failure.Conclusion:Of the tested substances for disinfection, 2% glutaraldehyde was the only substance that did not cause significant changes in the mechanical properties of orthodontic elastics and is considered as an alternative for elastic disinfection before its use.